Pengaruh Model Pembelajaran Mastery Learning terhadap Minat Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas XII SMA Negeri 1 Pahae Julu Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Sonita Panggabean; Johari Manik; Tiur Imeldawati (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
The aim of this research is to determine the positive and significant influence of the Mastery Learning learning model on interest in studying Christian Religious Education and Characteristics of Class XII Students at SMA Negeri 1 Pahae Julu, North Tapanuli Regency for the 2023/2024 Academic Year. The research method is quantitative descriptive inferential. The population is all class Data was collected using a positive closed questionnaire with 40 items. The results of data analysis show that there is a positive and significant influence of the Mastery Learning learning model on interest in studying Christian Religious Education and Characteristics of Class the positive value obtained is rxy = 0.594 > rtable(a=0.05,n=36) = 0.329. b) Testing a significant relationship obtained a value of tcount= 4.307 > ttable(a=0.05, dk=n-2=34)= 1.691. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂="14","69"+0.81X. b) Regression coefficient of determination test (r2) = 35.3%. Thus Ha is accepted and H0 is rejected.